An analysis of U.S. men`s javelin performance in international competition 1983-2017 - Babbit, D. (Track Coach, 2018)
The United States has had a moderate level of success in the men's javelin throw at major championships such as the Olympic Games and World Championships over the past 35 years, dating back to the first IAAF Championships back in 1983. However, in more recent times, this success has dropped off and it is now a rare occasion that a U.S. men's javelin thrower will even qualify for the final in a major championship. For a country of 326 million inhabitants with a strong sporting culture, especially with regard to throwing things, it is quite an underwhelming performance. It is obvious there must be some issues within the developmental system that are not allowing the U.S. to keep up with the other javelin throwing powers in producing world class javelin throwers. The purpose of this article will be to examine and discuss four critical elements that are thought to be part of this current state of affairs: 1. Characterize the development structure and recent trends within the U.S. men's javelin system. 2. Identify what levels of performance are needed to be competitive at the international level and the major championships. 3. Identify factors within the U.S. men's javelin development system that could be holding back greater development. 4. Offer potential solutions to meet these performance targets.